The Application of Nuclear Medicine - Giner Maslebu; Suryasatriya Trihandaru (Fakultas Sains dan Matematika Universitas Kristen Satya Wacana, 2016)
Currently, the practice of nuclear medicine in modern countries comprises a large number of procedures. It is applied to study function of organs/body systems, to visualize, to characterize, and to quantify the functional state of lesions and for targeted radionuclide therapy. This overview presents all kinds of application in nuclear medicine services. Instrumentation and radioactive/radiolabeled substances are the basic components for application. Biotechnology contributes to the development and production of biomolecules used in radiopharmaceuticals. As a diagnostic modality, imaging depicts radioactivity distribution as a function of time. Hybrid imaging provides more precise localization and definition of le-sions as well as molecular imaging cross validation. Counting tests study invivoorgan functions externally or assess analytes in the biologic samples. Radiopharmaceutical therapy can be applied directly into the lesion or targeted systemically. Nanotechnology facilitates targeting and opens the development of bimodal techniques. In addition, neutron application contributes to the advancement of nuclear medicine services, such as neutron activation analysis, neutron teletherapy and neutron capture therapy.